Impact of Currency Fluctuations on Foreign Direct Investment in Nigeria - Bukola Bolanle AWOGBENJA; Isibor John AREGAN (Communications of International Proceedings, 2022)
This research linked exchange rate, inflation and economic development with foreign direct investment in Nigeria, for the achievement of one of the objectives of vision 2020 of investment growth. The study examined how exchange rate, inflation, and economic development could help boost the nation’s foreign direct investment. Model, significant to the study, was adopted and modified. The research also utilized secondary data from 1986 till 2019 and adopted the multiple regression analysis to estimate the variables. The findings revealed inflation plus economic development all positively and significantly impact foreign direct investment, while exchange rate was negatively significant on impacting the dependent variable which was foreign direct investment. The study recommended, among others, that the government should improved exchange rate management policy and ensure stable exchange rate as a motivating factor for the attraction of foreign direct investment into Nigeria.
Keywords: Foreign Direct Investment; Exchange Rate; Inflation; Multiple Regression Technique; Economic Development